Smoking addiction and the risk of upper‐aerodigestive‐tract cancer in a multicenter case–control study. Issue 11 (21st June 2013) - Lee, Yuan‐Chin Amy; Zugna, Daniela; Richiardi, Lorenzo; Merletti, Franco; Marron, Manuela; Ahrens, Wolfgang; Pohlabeln, Hermann; Lagiou, Pagona; Trichopoulos, Dimitrios; Agudo, Antonio; Castellsague, Xavier; Betka, Jaroslav; et al.
<x xml:space="preserve">Abstract</x> Although previous studies on tobacco and alcohol and the risk of upper‐aerodigestive‐tract (UADT) cancers have clearly shown dose‐response relations with the frequency and duration of tobacco and alcohol, studies on addiction to tobacco smoking itself as a risk factor for UADT cancer have not been published, to our knowledge. The aim of this report is to assess whether smoking addiction is an independent risk factor or a refinement to smoking variables (intensity and duration) for UADT squamous cell carcinoma (SCC) risk in the multicenter case–control study (ARCAGE) in Western Europe. The analyses included 1, 586 ever smoking UADT SCC cases and 1, 260 ever smoking controls. Addiction was measured by a modified Fagerström score (first cigarette after waking up, difficulty refraining from smoking in places where it is forbidden and cigarettes per day). Adjusted odds ratios (ORs) and 95% confidence intervals (95% CIs) for UADT cancers with addiction variables were estimated with unconditional logistic regression. Among current smokers, the participants who smoked their first cigarette within 5 min of waking up were two times more likely to develop UADT SCC than those who smoked 60 min after waking up. Greater tobacco smoking addiction was associated with an increased risk of UADT SCC among current smokers (OR = 3.83, 95% CI: 2.56–5.73 for score of 3–7 vs. 0) but not among former smokers. These results may be consistent with a residual effect of smoking that was not captured by the questionnaire responses (smoking intensity and smoking duration) alone, suggesting addiction a refinement to smoking variables.